The joy of eternal life: a thorough description of the glory of eternal life in all its aspects, rightly and intelligibly drawn from god's Word ... - Nicolai, Philipp (Concordia Publishing House, 2021)
"The Lutheran Church commemorates three influential hymnwriters every October: Philipp Nicolai, Johann Heermann, and Paul Gerhardt. The Joy of Eternal Life sheds light on why Philipp Nicolai is still remembered over four hundred years after his death. During Nicolai's time as a pastor, he and his parishioners witnessed a horrendous plague claim the lives of four thousand people in five months. To comfort his people and counteract the belief at the time that death, loss, and despair rob human beings of God's goodness, presence, and love, he wrote this book. In it, he proclaims the glory of eternal life, God's love for His people, and our future resurrection in heaven. This books also includes two of his beloved hymns, "Wake, Awake, for Night Is Flying" and "O Morning Star, How Fair and Bright." Pastors, musicians, and those interested in Church history will appreciate reading Nicolai's popular work in English for the first time. Additionally, laity will appreciate the devotional nature of this work, which offers the comfort and consolation of Christ to those who are in despair"--